2000
DOI: 10.1021/ac9908647
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metal Cations, Metal Complexes, and Anions by Electrospray Mass Spectrometry in the Negative Ion Mode

Abstract: Pneumatically assisted electrospray mass spectrometry (ES-MS) is used in the negative ion mode for aqueous metal (M) solutions in an excess of hydrochloric or nitric acid, where the major anion X = Cl- or NO3-. A collision energy of approximately 20 eV removes anion-solvent clusters for most elements and leaves negative complex ions of the general form (Mn+Xn+1)-. Complexation with anions prevents charge reduction reactions at least to n = 3, even in cases where the third ionization energy of M greatly exceeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 40 publications
2
58
0
Order By: Relevance
“…These cluster ions have the general formula M x (NO 3 ) xϩ1 Ϫ (4%) are the only Cs nitrate species seen (data not shown). These cluster ions are also much more abundant from the heated capillary interface than from the curtain gas interface used previously [19]. In general, the intensity distributions of the Li isotope peaks in the cluster ions correspond to the expected patterns, as shown by the measured and calculated spectra for Li 8 (NO 3 ) 9 Ϫ in Figure 3.…”
Section: Ms and Cid Of Nitrate Complexes Of Group 1 And 2 Metalssupporting
confidence: 68%
See 2 more Smart Citations
“…These cluster ions have the general formula M x (NO 3 ) xϩ1 Ϫ (4%) are the only Cs nitrate species seen (data not shown). These cluster ions are also much more abundant from the heated capillary interface than from the curtain gas interface used previously [19]. In general, the intensity distributions of the Li isotope peaks in the cluster ions correspond to the expected patterns, as shown by the measured and calculated spectra for Li 8 (NO 3 ) 9 Ϫ in Figure 3.…”
Section: Ms and Cid Of Nitrate Complexes Of Group 1 And 2 Metalssupporting
confidence: 68%
“…Previous work from our group [19] showed that an excess of nitric acid can be used to produce M(NO 3 ) x Ϫ ions in negative ion mode. A single set of ion extraction conditions yields these ions for many elements.…”
Section: M(no 3 ) Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkali and transition-metal cations are known to form complexes with nitrate when an excess of NO 3 Ϫ is present in solution [42,43]. Generally, these complexes are of the form [(UO 2 )(NO 3 ) m ] Ϫ (m ϭ 1-3), although the formation of oxo-nitrate ([(UO 2 )(O)(NO 3 ) m ] Ϫ (m ϭ 1-2) and hydroxy-nitrate ([(UO 2 )(OH) n (NO 3 ) m ] Ϫ (n ϭ 1-2, m ϭ 0 -1) products are also observed [43].…”
Section: Negative Ions Containing Uranyl and Nitrate Generated By Esimentioning
confidence: 99%
“…Moreover, negative ionization is more susceptible to corona discharge [21,22]. Therefore, negative-ion mode MS detection of noncovalent anion-receptor complexes is less common than positive-ion mode, with the examples reported [23][24][25][26][27][28] for the detection of organic explosives. APCI presents some advantages compared with ESI in quantitative analysis such as higher dynamic range, and is considered rugged, easy to operate, and more tolerant of higher buffer concentrations (fewer matrix effects) [31].…”
mentioning
confidence: 99%